2021
DOI: 10.1002/asi.24540
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact of emotions on perceiving serendipitous information encountering

Abstract: Despite the potential importance of emotional aspects in information seeking, there is a lack of adequate attention to emotions' role in facilitating serendipitous information encountering. This paper contributes to this research gap by investigating the role of emotions during the process of perceiving and experiencing serendipitous information encountering in a controlled laboratory setting. The results show that applying a sketch game can stimulate participants' emotions. Our findings indicate that particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 86 publications
(123 reference statements)
0
2
0
Order By: Relevance
“…With respect to RQ2, while some prior research focused on how positive emotions would influence people to encounter more information (Sun et al, 2022), our results demonstrate the dynamic and potentially complex nature of the emotional responses. These findings indicate that while emotions may not always explicitly influence postencountering behaviours, encountered health information can significantly impact participants' emotions, sometimes leading to positive shifts but, in other cases, inducing negative feelings.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…With respect to RQ2, while some prior research focused on how positive emotions would influence people to encounter more information (Sun et al, 2022), our results demonstrate the dynamic and potentially complex nature of the emotional responses. These findings indicate that while emotions may not always explicitly influence postencountering behaviours, encountered health information can significantly impact participants' emotions, sometimes leading to positive shifts but, in other cases, inducing negative feelings.…”
Section: Discussionmentioning
confidence: 62%
“…The literature also suggests that emotional states can influence and be influenced by various factors. For example, (Sun et al, 2022) investigated the role of emotions and found that positive emotions influence the likelihood of encountering information.…”
Section: The Effect Of Emotionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serendipity is a phenomenon of unplanned encounter with different resources like information, people and things in various ways in different setup like library, museum, classroom, laboratory, World Wide Web, social media, database, repositories, television, radio or anywhere which leads to new ideas and discoveries (Liestman, 1992; Bjorneborn, 2008, 2017; McCay-Peet et al , 2014; Panahi et al , 2016). The classical definition of serendipity defines sagacity as an important ingredient where an individual should have intuitive skills, prepared mind and positive approach to insight the hidden phenomenon to experience serendipity (Van Andel, 1993; Carr, 2015). There could be varying perception of experiencing serendipity by different individuals in different situations, which can be an inevitable part of human experience and a latent phenomenon in everyone’s life.…”
Section: Introductionmentioning
confidence: 99%
“…According to 11th edition of Merriam Webster dictionary , the term serendipity is defined as “the faculty or phenomenon of finding valuable or agreeable things not sought for.” And according to 13th edition Collins dictionary , it is defined as “Serendipity is the luck some people have in finding or creating interesting or valuable things by chance.” Both definitions omit the term sagacity, which was an important concept in Walpole’s definition on serendipity that defines a prepared mind which has ability to make good judgments with their intuition, skills and observe the valued insights, and which, to the unprepared mind, might seem like irrelevant information. As quoted by Louis Pasteur, “ In the field of observation, chance favours only the prepared minds ” (Van Andel, 1993; Foster and Ford, 2003; Lawley and Tompkins, 2008; Rubin et al , 2011; Carr, 2015).…”
Section: Introductionmentioning
confidence: 99%